The penetration and ricochet of ogive-nosed rigid projectiles obliquely impacting metallic targets. Issue 1 (March 2022) - Vayig, Yaniv; Rosenberg, Zvi
A large number of 3D numerical simulations were performed in order to follow the trajectory changes of rigid CRH3 ogive-nosed projectiles, impacting semi-infinite metallic targets at various obliquities. These trajectory changes are shown to be related to the threshold ricochet angles of the projectile/target pairs. These threshold angles are the impact obliquities where the projectiles end up moving in a path parallel to the target's face. They were found to depend on a non-dimensional entity which is equal to the ratio between the target's resistance to penetration and the dynamic pressure exerted by the projectile upon impact. Good agreement was obtained by comparing simulation results for these trajectory changes with experimental data from several published works. In addition, numerically-based relations were derived for the penetration depths of these ogive-nosed projectiles at oblique impacts, which are shown to agree with the simulation results.